The potential of digital banking to handle the Covid-19 pandemic crisis: Modification of UTAUT model for Islamic finance industry - Alex Fahrur Riza (Faculty of Economics, Universitas Islam Indonesia, 2021)
Purpose – This research aims to examine the driving factors for the adoption of digital banking of Islamic banks during the COVID-19 pandemic, to explore the development of specific UTAUT2 model for Islamic financial technology, and to investigate factors that need to be improved in digital banking services of Islamic banks based on customer perspectives.Methodology – This research is divided into three. The first study is an empirical testing of UTAUT2 model modified by adding trust and satisfaction variables. The second study is an exploratory study of potential construct for the development of UTAUT model in Islamic Financial Technology. Third, it is an exploratory study aiming to identify problems and to search for policy advice to improve digital banking service of Islamic banks. This research used self-administered survey that involved 845 respondents from several cities in Indonesia. Open and closed question design was used to obtain complementary data. After that, the data were analyzed using SEM-PLS 7.0 and SPSS 23.Findings – The results of this study shows that people have trust, acceptance, and satisfaction on the digital banking service of Islamic banking technology. There are seven hypotheses in this study supported empirically. There are 20 factors that became the main reasons of customers to use the digital banking service of Islamic banking technology and 32 factors that needed to be improved by Islamic banks based on the customers’ perspective. After that, the researcher grouped them into seven policy advices for digital banking service of Islamic banking technology, where these factors can be taken into consideration to improve the competitiveness of the Islamic Finance Industry in Indonesia.Originality – In addition to testing and modifying the UTAUT2 model during the COVID-19 pandemic, this study also explores the possibility of new variables arising from customers’ perception, where the data will be used to submit new variables/models that are more specific to the acceptance of Islamic financial technology. Furthermore, this study also aims to explore several obstacles in the digital banking service of Islamic banking technology.